1998
DOI: 10.1073/pnas.95.9.5251
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ventricular function through gene transfer in vivo

Abstract: We used a catheter-based technique to achieve generalized cardiac gene transfer in vivo and to alter cardiac function by overexpressing phospholamban (PL) which regulates the activity of the sarcoplasmic reticulum Ca 2؉ ATPase (SERCA2a). By using this approach, rat hearts were transduced in vivo with 5 ؋ 10 9 pfu of recombinant adenoviral vectors carrying cDNA for either PL, ␤-galactosidase (␤-gal), or modified green f luorescent protein (EGFP). Western blot analysis of ventricles obtained from rats transduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
234
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(242 citation statements)
references
References 23 publications
8
234
0
Order By: Relevance
“…Whilst the majority of the transgene-positive cells were distributed throughout the ventricle, a third of the transgene-positive myocytes were distributed along the path of needle insertion. The results of all three studies 12,13 employing high pressure are consistent, suggesting that this is a truly reproducible method of gene delivery. The resulting grossly unphysiological pressure in the coronary artery that we have demonstrated presumably increases the fenestrations between the capillary endothelial cells, allowing transit of the adenovirus to the cardiac myocytes.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Whilst the majority of the transgene-positive cells were distributed throughout the ventricle, a third of the transgene-positive myocytes were distributed along the path of needle insertion. The results of all three studies 12,13 employing high pressure are consistent, suggesting that this is a truly reproducible method of gene delivery. The resulting grossly unphysiological pressure in the coronary artery that we have demonstrated presumably increases the fenestrations between the capillary endothelial cells, allowing transit of the adenovirus to the cardiac myocytes.…”
Section: Discussionmentioning
confidence: 60%
“…Using a similar model to Hajjar et al, 12 who performed experiments in the rat, we have demonstrated that intraventricular injection of recombinant adenovirus results in relatively efficient gene transfer. Although, in contrast to other interventions, this technique required an open chest, there were no associated alterations in baseline haemodynamics to suggest an artifactual increase in transfection efficiency.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations